The Most Common Taekwondo Kicks using the eShield at the 23rd Asian Taekwondo Championships, Vietnam 2018 - Abed Aljawad Bashar; Abdul Fattah Osama (European Scientific Journal, ESJ, 2018)
This paper focuses on identifying the most common taekwondo hits and kicks used by players at the 23rd Asian taekwondo championships, Vietnam 2018. A lot of researchers attended the 23rd Asian taekwondo championships and they analyzed the quarterfinals, semifinals, and finals for all weights classes for both males and female players. 111 matches (55 for male and 56 for females) were analyzed in this study. A form was used to process and analyze the matches. The results of this study showed that the turn kick attack with the rear leg at the abdominal level was the most commonly used kick, with the highest rate among male and female players (41.4% males and 46.3% females). Also, the percentage of the offensive kicks and strategies among males and females was very high compared with the defensive kicks and strategies. In this regard, the percentage of the offensive kicks among the males was 91%, whereas the rate of the defensive kicks reached 9%. On the other hand, the rate of the offensive kicks among the females was 88%, whereas the rate of the defensive kicks reached 12%. It was concluded that the offensive kicks at the abdominal level was the most commonly used kick among the players. In addition, there was a significant increase in the rate of the face kicks after the regulations amendments.